Millennials: Do They Need a Hero to Make Their Workplace More Welcoming? - Ully Rachmawati; Martina Dwi Mustika; Bertina Sjabadhyni (Universitas Katolik Soegijapranata, 2018)
This research sought to examine the influence of psychological capital on the relationship between job resources and work engagement on the millennial generation. By surveying 322 employees working in various types of organizations (government agencies, state-owned and private) in several major cities in Indonesia using mediation analysis to evaluate the hypothesis,this study reveals that psychological capital partially mediates the relationship between job resources and work engagement. The limitations faced during this study regard the method and research design used; hence, future studies may anticipate these issues. The findings further strengthen the significance of psychological capital on stimulating the level of millennials’ work engagement. In addition, job resources must not be neglected, since it also influences work engagement.